2019
DOI: 10.1088/1748-3190/ab0eb5
|View full text |Cite
|
Sign up to set email alerts
|

Canal neuromasts enhance foraging in zebrafish (Danio rerio)

Abstract: Aquatic animals commonly sense flow using superficial neuromasts (SNs), which are receptors that extend from the body's surface. The lateral line of fishes is unique among these systems because it additionally possesses receptors, the canal neuromasts (CNs), that are recessed within a channel. The lateral line has inspired the development of engineered sensors and concepts in the analysis of flow fields for submersible navigation. The biophysics of CNs are known to be different from the SNs and thereby offer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…The encoding and processing of the water flow stimuli may change with age, as the ratio of body size to stimulus features changes, and with the development of canal neuromasts (Van Trump and McHenry, 2008;Wada et al, 2014). As such, studying the ontogeny of the processing would be interesting, especially for the afferent neurons receiving information from the newly developed canal neuromasts, which have been linked to foraging in zebrafish (Carrillo et al, 2019). However, collecting such an ontological dataset would require imaging in ossified zebrafish, whose skulls and pigmentation preclude the use of one-photon light sheet microscopy.…”
Section: Coding Of Detailed Information About H-t Water Flowmentioning
confidence: 99%
“…The encoding and processing of the water flow stimuli may change with age, as the ratio of body size to stimulus features changes, and with the development of canal neuromasts (Van Trump and McHenry, 2008;Wada et al, 2014). As such, studying the ontogeny of the processing would be interesting, especially for the afferent neurons receiving information from the newly developed canal neuromasts, which have been linked to foraging in zebrafish (Carrillo et al, 2019). However, collecting such an ontological dataset would require imaging in ossified zebrafish, whose skulls and pigmentation preclude the use of one-photon light sheet microscopy.…”
Section: Coding Of Detailed Information About H-t Water Flowmentioning
confidence: 99%
“…Through the lateral line system, fish can detect these hydrodynamic cues and use them to make behavioral decisions ( Bleckmann and Zelick, 2009 ). For example, the detection of hydrodynamic pressure gradients that are generated by nearby prey movements allows predators to localize and approach the prey, thus improving their hunting success ( Coombs and Conley, 1997 ; Montgomery et al, 2002 ; Carrillo and McHenry, 2016 ; Carrillo et al, 2019 ). Similarly, a prey itself may rely on detecting the wakes produced by approaching or striking predators ( Stewart and McHenry, 2010 ; Stewart et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since early studies where prey fish were reported to rapidly accelerate from rest by bending into a C-shape and unfurling their tail [9][10][11][12], impulsive locomotion patterns have been the subject of intense investigation. Studying escape strategies of prey fish has led to the discovery of sensing mechanisms [13][14][15], dedicated neural circuits [16][17][18][19], and bio-mechanic principles [20,21]. From the perspective of hydrodynamics, several studies have sought to understand the C-start escape response and how it imparts momentum to the surrounding fluid [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%